Wpływologia. Międzywojenne dyskusje wokół „Pana Tadeusza” i futuryzmu jako elementy sporu o wpływy, zależności i plagiaty - Winiecka, Elżbieta (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2023)
The polemic over the role of literary sway-texts in the creative process took place in the early years of the interwar period. The beginning of the discussion was linked to the publication of the scholarly treatises on Pan Tadeusz by Stanisław Windakiewicz and Konstanty Wojciechowski. Critics and columnists pointed out to the above-mentioned the weakness of their analytical method, which – based on tracing the influence (swayness) of other works on Mickiewicz’s epic poem – was deemed to deprecate its stature and originality. Literary historian Wacław Borowy joined the polemic and in a series of articles explained in detail the arguments of researchers approaching the literary text from a scholarly perspective. Another participant in the discussion, Karol Irzykowski, formulated a categorical thesis on the plagiaristic nature of Polish literature, attacking the work of Polish Futurists as imitative and derivative. His criticism was countered by Anatol Stern and Bruno Jasieński. Stefan Żeromski and Stanisław Ignacy Witkiewicz also joined in the discussion. The former called for honesty in literature, the latter for making certain national culture and language was nurtured. The polemic over literary swayness coincided with work on Polish copyright law and also represented an early stage in the development of comparative and, albeit indirectly, intertextual studies.
Literary Swayness. Interwar Discussions on Pan Tadeusz and Futurism – a Polemic Over Imitaton, Reliance and Plagiarism